Management of dental waste in dental offices and clinics in Jeddah, Saudi Arabia - Sabbahi, Dania A.; El-Naggar, Hesham M.; Zahran, Mohammed H. (Journal of the Air & Waste Management Association (1995), 2020)
Management of dental wastes became a recent challenge facing health care practitioners and is one of the highly-sensitive environmental problems. The main purpose of this study was to assess oral health care provider's knowledge and behavior about dental waste management and evaluate their behavior toward it. A cross-sectional descriptive study was conducted on 314 dental health care providers working in four dental colleges, and 20 private dental clinics in Jeddah, Saudi Arabia. A pretested questionnaire composed of close-ended questions was used. The mean age of the participants was 27 years. About 78% of the participants reported that they were working in the public sector. Only 33.4% of the study sample received professional training on waste management. The mean behavior and knowledge scores were 3.7 ± 1.3 (out of 6) and 1.4 ± 1.3 (out of 8), respectively. Statistically significant association was noted between gender and knowledge scores but not between gender and behavior scores. On the other hand, statistically significant associations were noted between both knowledge and behavior scores and rank of the participant, type of practice, and years of experience. Oral health care providers' knowledge about the effective procedure that should be followed for segregating, collecting, transporting, and treating dental waste was weak and substandard. There is an urgent need to develop policies and regulations for dental waste management in Saudi Arabia. Implications: This study shed light for the first time on the knowledge and behavior of dentists in Jeddah, Saudi Arabia in regard to the dental waste management. Participants knowledge and behavior in regard to dental waste segregation, collection, transportation, and treatment were determined to be week and substandard. Currently, different procedures related to dental waste management in health care facilities are not clearly described. The urgent need for the development of policies and regulations for the dental waste management is obvious. This study can be a starting point for future nation-wide surveys to assess knowledge, behavior and practices related to dental waste management among oral health care providers. In addition, more efforts should be directed to incorporate this subject into dental curriculum and continuous education courses.